Does Having a Master's in Public Health (MPH) Improve Physician Assistants' Ability to Address the Social Determinants of Health in Their Clinical Practice? - Gayle Cummings; Carinne Brody; Annette Cremo (Shahid Beheshti University of Medical Sciences, 2021)
Background: There is mounting evidence that clinicians need to address the social determinants of heath (SDOH) in their practice. Physician Assistants (PAs) who complete a joint degree with a Master of Public Health (MPH) may be able to address the SDOH in their practice better than those who do not have the degree. The primary aim of this study was to determine whether or not having a Master in Public Health (MPH) improves PAs' ability to address the SDOH in their clinical practice. Methods: A cross-sectional study was conducted with 25 practicing PAs who were jointly trained with the MPH degree and 32 practicing PAs who were not jointly trained. An online survey was administered to a gather SDOH knowledge, attitude and behavior data using an adapted 13-item SDOH scale. Results: This study found that jointly trained PA/MPH clinicians reported significantly more perceived knowledge about SDOH (37.6 vs 31.1; P = .028), were more likely to identify SDOHs as important to their patients' health (38.6 vs 32.9; P = .035), were more likely to intend to address SDOH with their patients' (29.7 vs 23.5; P = .031) and reported feeling more comfortable talking about SDOH with their patients (3.75 vs 3.2; P = .05) despite no significant differences in reported barriers to addressing SDOH. Conclusion: These findings suggest that joint clinical training with the MPH can positively impact PAs ability to address the SDOH in their clinical work and lays the groundwork for future research.